Analysis of energy orchards’ profitability - Csipkés, Margit; Nagy, Lajos (Acta Agraria Kaposváriensis, 2010)
Considering the environmental, climatic and soil endowments of Hungary, it is suitable for alternative utilization of biomass, and for the increase of it for energetic purposes, which promotes the production of energy crops. In the plan of the European Union it can be seen that the role of renewable energy sources in the energy production will increase significantly that can improve considerably the environmental judgment of Hungary. A possibility of producing energy form biomass is energy orchards. Recently, for an agricultural producer the planting of an energy orchard can be considered very risky, since the return of orchards is a critical point in the course of production. Therefore, we considered important to examine the profitability of these cultures. In the course of our research we made the cost-benefit analyses for locust, poplar and Swedish willow for a period of 12 years. We stated that Swedish willow is the most profitable, which can be attributed to the realitvely high yield. Poplar is the least recommended for establishing energy orchards despite the fact that it has a two-year cutting cycle.